The Indian Civil Service and Indian Foreign Policy, 1923-1961 - Das Gupta, Amit (Taylor & Francis, 2021)
Nehruvian Diplomacy, Indian diplomacy, Cold War politics, decolonisation, British India, World War II, Gandhi